Effective Scheduling of Supervisors at University Level: Examining Its Influence on Researcher Motivation, Procrastination Behavior and Academic Success - Dr. Sidra Kiran; Nazia Nazir; Humna; Wajid Mahnaz (Research Journal of Psychology, 2025)
The phrase "time management" became widely used in the 1950s and 1960s to refer to a tool that helped managers better utilize their time. The tool's dos and don'ts were derived from real-world experiences. While the phrase implied time management, in practice, time management is applied to activities. When deciding what to accomplish, how much time to spend on each activity, how to finish chores faster, and when to finish particular tasks, time management is self-management that specifically takes time into account. The study aimed at “Effective Scheduling of Supervisors At University Level: Examining Its Influence On Researcher Motivation, Procrastination Behavior, and Academic Success”. The objectives of the study were 1) To identify and evaluate the time management strategies employed by supervisors in university settings, 2) To assess the academic performance of researchers based on key performance indicators in higher education, 3) To investigate the correlation between supervisors' time management strategies and the academic performance of researchers, highlighting potential influencing factors. A quantitative research design was employed, targeting PhD faculty from public and private universities in Rawalpindi and Islamabad. Eighteen universities were nominated by using simple random sampling technique. Data were collected through a self-developed questionnaire, distributed to students and faculty members and analyzed using descriptive and correlation statistical techniques. The findings of the study show that Supervisors, who effectively implemented time management strategies, experienced a 27.7% improvement in their research teams' performance, particularly in thesis completion and publication rates. The most influential strategies were prioritization and procrastination reduction, significantly enhancing research productivity. Additionally, stress management and effective communication played a crucial role in maintaining workflow efficiency and meeting deadlines. Hence, it is recommended that supervisors undergo training in structured time management techniques, including prioritization and procrastination reduction, to enhance research productivity. Institutions should provide workshops on stress management and effective communication to improve supervisory efficiency. Furthermore, supervisors should adopt digital tools for task scheduling and progress tracking to ensure smooth research workflows and timely completion of academic tasks.